THE INFLUENCE OF FAMILY ENVIRONMENT AND LEARNING STYLE ON TAX ADMINISTRATION LEARNING OUTCOMES AT SMKN 17 JAKARTA - Lusiana, Vivi Intang; Zulaihati, Sri; Sumiati, Ati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2020)
This study aims to determine the effect of the family environment and learning styles on learningoutcomes in the subject of Tax Administration at 17 Jakarta Vocational High Schools. This research wasconducted on students of 17 Vocational High Schools Jakarta. The population of this research was 85students of class XI and XII of 17 Jakarta State Vocational High School majoring in FinancialAccounting and Institutions. The sampling technique used strata random sampling in order toobtain a sample of 85 students. The data analysis technique used is multiple regression test,requirements test, hypothesis test, and determinant coefficient. The multiple regression test states thatthe family environment and learning styles have a positive effect on learning outcomes. Therequirements test performed showed the results, namely the data were normally distributed andlinear. Based on the results of hypothesis testing, it can be concluded that all hypotheses are accepted.The determinant coefficient in this study is 11.1%, which indicates that the family environment andlearning style affect learning outcomes while the rest is influenced by other factors not examined. Thisresearch was conducted during the pandemic so that the independence of students in learning is high,because in this case students are motivated to learn more independently through various online lessonsthat can be accessed easily via students' smartphones. This makes students more flexible inobtaining various materials and training needed.